Sailing in a Concrete Boat Retrosspective and Prospecctive - Leggo, Carl.; SpringerLink (Online service) (Rotterdam : SensePublishers : Imprint: SensePublishers, 2012)
Sailing in a Concrete Boat: A Teacher$1 (Bs Journey is a novel-length narrative composed in a sequence of short fictions and poetry linked by recurring characters, themes, events, and setting. The narrative explores the experiences and emotions of a school teacher named Caleb Robinson. He teaches in a conservative church-administered school in a rural Newfoundland town called Morrow$1 (Bs Cove. Caleb struggles to understand what it means to be a teacher, husband, lover, friend, father, Christian, and human being. Sailing in a Concrete Boat raises many questions about pedagogy as questioning, freedom of expression, conservative religious beliefs, breaking silences, and curriculum as cultural reproduction instead of cultural transformation. Above all, Sailing in a Concrete Boat seeks to narrate the complex lived experiences of a school teacher as he questions love, family, community, vocation, well-being, romance, spirituality, authority, silence, truth, and identity. In order to make sense of his tangled living experiences, Caleb is always remembering and researching his past in order to write and rewrite his future. Sailing in a Concrete Boat will be a valuable resource in both undergraduate and graduate courses in teacher education, curriculum and pedagogy, life writing, poetic inquiry, arts-based research, and narrative inquiry. Social Fictions Series Editorial Advisory Board Carl Bagley, University of Durham, UK Anna Banks, University of Idaho, USA Carolyn Ellis, University of South Florida, USA Rita Irwin, University of British Columbia, Canada J. Gary Knowles, University of Toronto, Canada Laurel Richardson, The Ohio State University (Emeritus), USA Carl Leggo is a poet and professor in the Department of Language and Literacy Education at the University of British Columbia where he teaches undergraduate and graduate courses in writing and narrative inquiry. His books include: Growing Up Perpendicular on the Side of a Hill; View from My Mother$1 (Bs House; Come-By-Chance; Teaching to Wonder: Responding to Poetry in the Secondary Classroom; Lifewriting as Literary Metissage and an Ethos for Our Times (co-authored with Erika Hasebe-Ludt and Cynthia Chambers); Being with A/r/tography (co-edited with Stephanie Springgay, Rita L. Irwin, and Peter Gouzouasis); Creative Expression, Creative Education (co-edited with Robert Kelly); Poetic Inquiry: Vibrant Voices in the Social Sciences (co-edited with Monica Prendergast and Pauline Sameshima); and Speaking of Teaching (co-authored with Avraham Cohen, Marion Porath, Anthony Clarke, Heesoon Bai, and Karen Meyer).s
Keywords: Education; Education; Education (general).